Loaded : money, psychology, and how to get ahead without leaving your values behind - Newcomb, Sarah C. (Tantor Audio, 2019)
YOUR MOST VALUABLE ASSET ... IS YOU. LOADED WILL TEACH YOU HOW TO MAKE THE MOST OF IT. Based on decades of research and years of hands-on experience with people from all walks of life, LOADED is a must-read for anyone who finds themselves caught between the desire to thrive financially and the complex emotions and conflicting priorities that money so often brings to our lives. You will learn to: &#9679 Check your stories. Pinpoint and change beliefs that hold you back. &#9679 Choose your strategies. Learn how to align your money with your needs. &#9679 Cultivate your value. Put your unique resources to use and earn more. Deeply researched, yet written in an approachable, conversational tone, LOADED offers insight into how your personal experiences have shaped your financial attitudes, and how you can build a healthier relationship with money.